1995
DOI: 10.1152/ajplung.1995.269.4.l520
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fluid-phase endocytosis in alveolar macrophages

Abstract: We investigated whether fluid-phase endocytosis in rabbit alveolar macrophages (AM) was regulated by alterations in intracellular adenosine 3',5'-cyclic monophosphate (cAMP). Suspensions of freshly isolated AM were incubated with anionic dextrans (mol mass = 10 kDa), coupled to fluorescein isothiocyanate (FITC), at either 37 or 4 degrees C. There was a rapid increase in AM-associated fluorescence, quantified by laser flow-cytometry and video microscopy during the first hour of incubation at 37 degrees C, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…An alternate, non-concentrating transport mechanism is pinocytosis, which delivers droplets of the extracellular fluid to the endosomal apparatus in alveolar macrophages (Pataki et al, 1995). As evaluated using dextran uptake, the PMNLs are the most active cells in this respect in among several tested cell types (including the myeloid cell lines PLB 985 and U937 with K M values for quinacrine transport similar to that of lymphocytes, data not shown), with a characteristic subcellular granular distribution similar to that of quinacrine (compare Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternate, non-concentrating transport mechanism is pinocytosis, which delivers droplets of the extracellular fluid to the endosomal apparatus in alveolar macrophages (Pataki et al, 1995). As evaluated using dextran uptake, the PMNLs are the most active cells in this respect in among several tested cell types (including the myeloid cell lines PLB 985 and U937 with K M values for quinacrine transport similar to that of lymphocytes, data not shown), with a characteristic subcellular granular distribution similar to that of quinacrine (compare Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid phase endocytosis (pinocytosis) was evaluated in pure population of leukocytes or myeloid cell lines by measuring the uptake of dextran (40 kDa) conjugated to rhodamine B (SigmaAldrich; final concentration in HBSS 1 mg/ml; adapted from Pataki et al, 1995). After a 30-min incubation at 37°C, the cells were centrifuged and washed prior to being photographed (green fluorescence and transmission, 1000×).…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the beneficial effects of b 2 -agonists on the alveolar epithelium, activation of b 2 AR (94) has an inhibitory effect on the function of alveolar macrophages where they diminish motility (95) via increased levels of cAMP, which has also been reported to result in diminished fluid phase endocytosis (96) and phagocytosis function (97). There is a great body of experimental data indicating that specific and nonspecific b-agonists enhance AFC in experimental models of cardiogenic and noncardiogenic pulmonary edema (1, 9, 61).…”
Section: Other Functionsmentioning
confidence: 99%
“…It has been demonstrated that macrophages express a small number of P2X4 at the cell surface [13,14,28] with a normalised mean current density of only 1-2 pA/pF [13]. Macrophages are known to have high rates of endocytosis [29] and rapidly turn over their repertoire of cell surface receptors. Expression of dynamin 2 in macrophages [25] may contribute to the limited surface expression of P2X4.…”
Section: Discussionmentioning
confidence: 99%